2019
DOI: 10.1080/13674676.2019.1639649
|View full text |Cite
|
Sign up to set email alerts
|

Doctrinal dialogues: factors influencing client willingness to discuss religious beliefs

Abstract: Religious beliefs are an important part of daily life for many individuals; however, these beliefs are often not discussed in therapy settings. As a result, clients and clinicians may encounter barriers to treatment and be unable to harness potentially beneficial aspects of the religious belief system. The current study investigated factors influencing client willingness to discuss religious beliefs with a therapist, with the factors of interest being perceived clinician cultural humility (PCH), religious outl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Client-perceived therapist cultural humility was linked to positive working alliances, therapy continuance, expected treatment effectiveness (Hook et al, 2013), positive treatment outcomes (Kivlighan et al, 2019;Owen et al, 2014Owen et al, , 2016, higher psychotherapist competence ratings (DeBlaere et al, 2019), lower frequency and lower impact of racial microaggressions (Hook et al, 2016), lower colourblind racial attitudes (Haywood Stewart, 2019), greater prosocial justice advocacy attitudes (Chase, 2021) and willingness to disclose and discuss one's religious beliefs (Judd, 2017). Conversely, lack of participant-perceived therapist cultural humility was associated with weaker working alliances and more therapeutic ruptures (Davis et al, 2016).…”
Section: Overall Relationshipmentioning
confidence: 99%
“…Client-perceived therapist cultural humility was linked to positive working alliances, therapy continuance, expected treatment effectiveness (Hook et al, 2013), positive treatment outcomes (Kivlighan et al, 2019;Owen et al, 2014Owen et al, , 2016, higher psychotherapist competence ratings (DeBlaere et al, 2019), lower frequency and lower impact of racial microaggressions (Hook et al, 2016), lower colourblind racial attitudes (Haywood Stewart, 2019), greater prosocial justice advocacy attitudes (Chase, 2021) and willingness to disclose and discuss one's religious beliefs (Judd, 2017). Conversely, lack of participant-perceived therapist cultural humility was associated with weaker working alliances and more therapeutic ruptures (Davis et al, 2016).…”
Section: Overall Relationshipmentioning
confidence: 99%
“…Further, therapists could combat assumptions of religious homogeneity by acknowledging the variability within religious groups and exploring the connections between clients’ beliefs and presenting concerns in a curious, open manner. Indeed, therapist demonstrations of cultural humility, such as comments showing openness and acceptance, were associated with a lower frequency of microaggressions in psychotherapy (Hook et al, 2016) and led to greater client willingness to discuss religion (Judd, 2019), which could create opportunities to leverage their beliefs in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the way the therapist delivered the intervention may have impacted the client’s perception of the therapist’s humility. Judd (2019) found clients only brought up R/S issues in psychotherapy if they perceived their therapists to be culturally humble. While we did not ask Emily or Rachel to rate Brad or Julie’s cultural humility, the fact that both clients engaged their therapists on R/S issues suggests that they found their therapists culturally humble; this is consistent with their overall high alliance and outcome scores by the end of treatment and prior findings suggesting an association between cultural humility related to R/S and client outcomes (Owen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Namely, when clients saw their therapist as culturally humble in regard to their religious/spiritual identity, they also reported a stronger therapy alliance therapeutic alliance and better client outcomes (Owen et al, 2014). Judd (2019) found that participants reported being more likely to bring up R/S issues with a therapist if they perceived the therapist to be high on cultural humility, suggesting that a humble stance in session may lead to client-initiated cultural opportunities. Finally, a qualitative study investigating religious clients’ perceptions of secular therapy found that clients felt reassured about their treatment effectiveness when their therapist demonstrated an openness (i.e., comfort) to discuss R/S issues and felt more distressed when therapists ignored client prompts to discuss R/S issues (i.e., missed cultural opportunity; Mayers et al, 2007).…”
Section: Mco and Religion/spiritualitymentioning
confidence: 99%